Translation as Genesis (TEST Ticontre. Theory Text Translation, 2015)
Translation of literature is generally understood as a copy of an original. As such, it finds itself compared negatively to the original; judged and found lacking either the style or meaning of the original text it was seeking to translate. However, this paper will explore the relationship between the text and its translation through the work of Jacques Derrida and his neologisms such as the supplement and différance in addition to the work of Walter Benjamin. Through understanding the translation as a supplement, this paper will explore whether the original text was complete in and of itself. Through this and Derrida’s understanding of the play of language, I argue that translation can be understood as the palingenesis of literature, as it is only through translation that literature is reborn and lives on. Moreover, this paper will conclude with an examination of Blanchot’s distinction between the Book and the book in order to argue that literature is in itself a form of translation. Thus, the relationship between translation and literature is one of a cycle of genesis and palingenesis, as translation finds itself at both the beginning and continual rebirth of literature.La traduzione letteraria viene generalmente intesa come la copia di un originale. In quanto tale essa viene considerata negativamente in rapporto a quest’ultimo, giudicata manchevole quanto a stile o contenuto rispetto al testo originale che cerca di tradurre. Questo articolo intende esaminare la relazione tra il testo e la sua traduzione attraverso l’opera di Jacques Derrida e i suoi neologismi, come supplemento e différance, e sulla scorta degli studi di Walter Benjamin. Considerando la traduzione come un supplemento, l’articolo indaga se l’originale sia completo in e di per se stesso. Attraverso questo concetto e la prospettiva di Derrida sul gioco del linguaggio, la tesi sostenuta è che la traduzione possa essere considerata come palingenesi della letteratura, dal momento che è solo attraverso la traduzione che la letteratura rinasce e continua a vivere. Infine, l’articolo si conclude con un esame della distinzione di Blanchot tra Libro e libro al fine di sostenere che la letteratura è già in sé una forma di traduzione. Pertanto, il rapporto tra traduzione e letteratura si configura come un ciclo di genesi e palingenesi, nel quale la traduzione si trova tanto al cominciamento quanto nel continuo rinascere della letteratura.